Srednjeveška Tržačanka v ogledalu mestnega statuta - Mihelič, Darja (Etnolog. Nova vrsta (Ljubljana), 1997)
Based on the publication of one Trieste statute the article presents the condition of the town's women in the Middle Ages: from childhood to maturity, their position in the family and in marriage, their legal and business capacity. They are also mentioned as possible victims or perpetrators of criminal acts.
Keywords: Mihelič, Darja; Trst; zgodovinski pregledi; žensko vprašanje; Middle Ages; srednji vek; ženske; woman; statuti; ethnology; etnologija; ljudsko življenje